2010
DOI: 10.1093/brain/awq058
|View full text |Cite
|
Sign up to set email alerts
|

Resting state networks change in clinically isolated syndrome

Abstract: Task-functional magnetic resonance imaging studies have shown that early cortical recruitment exists in multiple sclerosis, which can partly explain the discrepancy between conventional magnetic resonance imaging and clinical disability. The study of the brain 'at rest' may provide additional information, because task-induced metabolic changes are relatively small compared to the energy use of the resting brain. We therefore questioned whether functional changes exist at rest in the early phase of multiple scl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
232
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 224 publications
(261 citation statements)
references
References 55 publications
26
232
2
1
Order By: Relevance
“…However, we also confirmed the bilateral parahippocampal gyri, right amygdala, left thalamus and left midtemporal pole as more strongly connected in RRMS patients (Richiardi et al, 2012). Such selective increased FC has been reported by several other studies as well (Bonavita et al, 2011;Dogonowski et al, 2013;Hawellek et al, 2011;Richiardi et al, 2012;Rocca et al, 2012;Roosendaal et al, 2010) and has been interpreted as a compensatory mechanism (Bonavita et al, 2011;Roosendaal et al, 2010) because activation studies have shown increased activity in regions devoted to the task and the recruitment of additional regions in MS patients (Pantano et al, 2002;Rocca et al, 2005). It is however also possible that these increases originate from a loss of flexibility in functional interactions, rather than as a compensatory mechanism (Hawellek et al, 2011).…”
Section: Stationary and Dynamic Fc In Rrms Patientssupporting
confidence: 90%
See 2 more Smart Citations
“…However, we also confirmed the bilateral parahippocampal gyri, right amygdala, left thalamus and left midtemporal pole as more strongly connected in RRMS patients (Richiardi et al, 2012). Such selective increased FC has been reported by several other studies as well (Bonavita et al, 2011;Dogonowski et al, 2013;Hawellek et al, 2011;Richiardi et al, 2012;Rocca et al, 2012;Roosendaal et al, 2010) and has been interpreted as a compensatory mechanism (Bonavita et al, 2011;Roosendaal et al, 2010) because activation studies have shown increased activity in regions devoted to the task and the recruitment of additional regions in MS patients (Pantano et al, 2002;Rocca et al, 2005). It is however also possible that these increases originate from a loss of flexibility in functional interactions, rather than as a compensatory mechanism (Hawellek et al, 2011).…”
Section: Stationary and Dynamic Fc In Rrms Patientssupporting
confidence: 90%
“…The identified brain regions are largely consistent with those in a previous study by our group, which aimed at discriminating between HC subjects and RRMS patients based on stationary FC (Richiardi et al, 2012); i.e., the left Heschl's gyrus, right rolandic operculum, and right superior parietal gyrus, were identified as being more strongly connected in HC subjects in both studies. Reduced stationary FC in MS patients is indeed commonly observed and is thought to stem from structural damage (Bonavita et al, 2011;Lowe et al, 2002;Richiardi et al, 2012;Roosendaal et al, 2010). However, we also confirmed the bilateral parahippocampal gyri, right amygdala, left thalamus and left midtemporal pole as more strongly connected in RRMS patients (Richiardi et al, 2012).…”
Section: Stationary and Dynamic Fc In Rrms Patientssupporting
confidence: 73%
See 1 more Smart Citation
“…Studies have highlighted alterations to the DMN (Buckner et al, 2008) associated with multiple sclerosis (Roosendaal et al, 2010;Bonavita et al, 2011). To investigate this effect more specifically in our data, a subnetwork of the whole-brain graph comprising regions that are part of the DMN was defined (based on the work of Buckner et al (2008), and including the ventral and medial prefrontal cortex, the posterior cingulate and retrosplenial cortex, inferior parietal lobule, lateral temporal cortex, and hippocampal formation.…”
Section: Connections Outside the Default-mode Network Are Also Informmentioning
confidence: 99%
“…Weaker DMN connectivity in the ACC of MS patients was also reported by Bonavita et al (2011) using independent component analysis of fMRI resting-state data. Roosendaal et al (2010) investigated fMRI restingstate networks in patients with clinically isolated syndrome (CIS) and patients with RRMS and observed an increased synchronisation of some resting-state networks in CIS patients which disappeared in those with RRMS, suggesting initial functional compensation that is lost with disease progression. Using ICA and seed correlation, Jones et al (2011) showed significant differences in connectivity at rest between a single MS patient with an important thalamic lesion and a group of controls, in particular in the default mode network.…”
mentioning
confidence: 99%